The Role of Nonverbal Codes in Intercultural Communication - Bakić Mirić, Nataša M.; Janković, Anita V. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Nonverbal communication as one of the most important requirements of the communicative competence of each individual is an integral part of intercultural communication, i.e., communication between people who come from different cultures. Although language is an effective means of transmitting information, in the process of communication, in addition to verbal messages, hidden messages are also transmitted via nonverbal codes.Although many nonverbal codes can be considered universal, most are learned in a particular cultural space and are therefore culturally specific. Hence, it is necessary to look for broader cultural patterns in nonverbal behaviour instead of trying to identify cultural differences because it reduces their complexity and can lead to misunderstandings in intercultural communication because it is the understanding of intercultural communication that assumes that people are basically cultural beings.Understanding nonverbal codes is, therefore, a key factor in the communication process both intraculturally and interculturally. Bearing in mind that nonverbal codes are culturally different, this paper analysed their role in intercultural communication, their universality, and classification through examples.
Keywords: nonverbal communication; intercultural communication; nonverbal codes; cultural space